Factors that Affect Online Repurchase Intention at Tokopedia - Chyntia Harijono (iBuss Management, 2018)
Internet shopping or e-commerce has become a phenomenon to do online transactions. In Indonesia, e-commerce sales is expected to keep increasing from year to year, showing that e-commerce has a potential growth in Indonesia. In fact, there are a lot of Indonesian e-commerce companies which compete with each other. Tokopedia as one of the e-commerce player in Indonesia needs to know factors that affect the online Repurchase intention in order to survive in the competition. Thus, this research is aimed to help Tokopedia in finding the factors that are significant to influence online Repurchase intention at Tokopedia.This research is conducted by spreading questionnaires to 119 respondents who have bought a product in Tokopedia’s website. The results shows that only trust that has significant influence toward online Repurchase intention and customer satisfaction. Furthermore, Path and Sobel analysis results show that customer satisfaction only mediates the influence of trust toward online Repurchase intention.Keywords:Online repurchase intention, customer satisfaction, trust, e-commerce